2019
DOI: 10.2337/dc19-0762
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Connectivity Abnormalities in Prediabetes and Type 2 Diabetes: The Maastricht Study

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 35 publications
(35 reference statements)
3
44
0
Order By: Relevance
“…In the Maastricht Study, Laura W. Vergoossen et al ( 37 ) used whole-brain white matter tractography to find that prediabetes, T2DM, and continuous measures of hyperglycemia are associated with fewer white matter connections and weaker organization of white matter networks.…”
Section: Resultsmentioning
confidence: 99%
“…In the Maastricht Study, Laura W. Vergoossen et al ( 37 ) used whole-brain white matter tractography to find that prediabetes, T2DM, and continuous measures of hyperglycemia are associated with fewer white matter connections and weaker organization of white matter networks.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the authors examined the number of WM connections (node degree) between several brain regions as well as topology (graph measures, including clustering coefficient—number of connections between nearest neighbors of a region as a proportion of total possible connections, labeled as “clusters”; local efficiency—average efficiency of local clusters; global efficiency—the inverse of the average shortest path length; and communicability—a measure of all possible paths of communication between regions) (Vergoossen et al, 2020). Results showed that individuals with prediabetes had significantly lower node degrees (i.e., fewer WM connections) compared to those with normoglycemia (Vergoossen et al, 2020). Prediabetics also had smaller tract volumes of several intrahemispheric connections associated with aging, compared to those with normoglycemia (Vergoossen et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that individuals with prediabetes had significantly lower node degrees (i.e., fewer WM connections) compared to those with normoglycemia (Vergoossen et al, 2020). Prediabetics also had smaller tract volumes of several intrahemispheric connections associated with aging, compared to those with normoglycemia (Vergoossen et al, 2020). In addition, the local efficiency and clustering coefficient were lower (i.e., weaker local connectivity) in prediabetics compared to those with normoglycemia, although these effects diminished in fully adjusted models (Vergoossen et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step was to perform connectivity analysis to obtain white matter tracts from and to all the AAL2 brain regions. A previous study of our group confirmed the robustness of tract volume as a measure for the edge weighting [28]; therefore, for each connection, the tract volume was calculated as the number of voxels visited by at least one tract between the areas concerned multiplied by the voxel volume (in mm 3 ) (as previously described [32]). The obtained connectivity matrix with tract volumes was normalized to intracranial volume to reduce inter-subject variation [37].…”
Section: Image Preprocessingmentioning
confidence: 99%